PENGARUH pH DAN WAKTU KONTAK TERHADAP ADSORPSI METILEN BIRU MENGGUNAKAN SERBUK GERGAJI KAYU JATI - Baunsele, Boy (ALOTROP, 2024)
Methylene blue is a dye used in the textile industry, especially in fabric dyeing, but it has a negative impact on the environment. Various methods have been taken to reduce or even eliminate these pollutants in the environment. This research aims to examine the ability of teak sawdust to act as an adsorbent for methylene blue dye. So far, teak wood sawdust as waste that has only been burned has not been used properly and can be used as an adsorbent for the adsorption of methylene blue. This research using the adsorption method uses an 80 mesh adsorbent. The results showed that adsorption of methylene blue occurred optimally at pH 6, with an adsorption percentage of 99.26% and an optimum contact time of 30 minutes for adsorption with an adsorption percentage of 99.4% and an adsorption capacity of 2.045 mg g-1.